Far-from-equilibrium nanoparticle assemblies : patterns, transport and dynamics - Blunt, Matthew Oliver (2007)
This work is centered on the study of self-organisation and pattern formation in a prototypical nanostructured system, namely colloidal nanoparticle assemblies. The particular system chosen for investigation, Au nanocrystals spin cast onto silicon substrates from a solvent, despite being chemically rather simple exhibits a rich variety of complex patterns. In the majority of experiments discussed in this thesis, far-from-equilibrium conditions are attained by a spin-casting process which drives rapid solvent evaporation. A systematic study was carried out to determine the various factors affecting the morphology of nanoparticle assemblies produced in this manner. These factors include the concentration of the nanoparticle solution, the particular solvent used, and the chemical/ physical nature of the substrate. Changing these variables can affect both the strength of interactions between individual nanoparticles and between nanoparticles and the substrate. The various morphologies of the nanoparticle structures produced were studied using atomic force microscopy (AFM). Particular attention is paid to the role of the substrate's surface chemistry in pattern selection. A range of different substrates are used to gauge the influence of differing surface chemistries. In addition, scanning probe lithography was employed to microscopically pattern surfaces. This facilitated the observation of effects caused by the presence of two radically different surface chemistries in the micron size range. This patterning process provides the experimenter some measure of control over the morphology of the nanoparticle assembly, allowing the enforcement of predefined length scales onto the network. Simulations of drying nanocrystal films produced using code written by Martin et al [1] have been shown to accurately reproduce the experimental results. These simulations are used to develop theoretical explanations of the experimental data in terms of the varying solvent evaporation rate on the substrate and the manner by which the solvent dewets on chemically and topologically differing areas of a surface. A remarkable probe-induced coarsening of nanoparticle assemblies by repetitive scanning with an AFM probe has been studied. Repeated scanning of colloidal nanoparticle systems causes the irreversible growth of nanoparticle assemblies. The size distribution of structures produced by this growth is shown to be self-similar. With the size of the domains growing with a power law dependence on scan time. From a combination of these results the growth of structures is explained using a model of coarsening based on cluster diffusion and coalescence. This model is subtly different from coalescence in a thermally driven system due to the novel nature of the mechanical coarsening process. Electrical transport through different array morphologies produced via the spin-coating process was studied using D. C. electrical measurements and electrostatic force microscopy (EFM). Measurements over temperatures ranging from 4.5K to room temperature were made. Variations in the manner that power law scaling of the conduction behaviour alters for different arrays is linked to the topological characteristics of the arrays.